INFORMATION TECHNOLOGY-BASED MANAGEMENT EDUCATION IN VOCATIONAL HIGH SCHOOLS - Rita Aryani; Leroy Holman Siahaan (Universitas Padjadjaran, 2020)
This study aims to analyze the role of information technology-based management education in vocational schools. The implementation of technology was conducted in several schools, covering managerial aspects as well as academic aspects. This research utilizes a qualitative approach and descriptive method. Data obtained through literature review and analyzed descriptively and qualitatively. The results show that technology-based management education is essential to provide information to support and facilitate the management and academic processes daily. Schools must invest in technology-based school systems to increase the effectiveness and efficiency of school management generally.